HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN PERILAKU PENCEGAHAN PENULARAN TBC PADA MAHASISWA DI ASRAMA MANOKWARI SLEMAN YOGYAKARTA - Djannah, Siti Nur; Suryani, Dyah; Purwati, Dian Asih (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2009)
Background: Based on field reports and findings of the 2008 Health Office Yogyakarta, the number of TB patients in DIY reached 1.141orang. In general, the increase in TB patients in the last seven years approximately 15 percent, Noted there are 428 positive patients with TB in the city of Yogyakarta. Meanwhile, patients who went to the city of Yogyakarta to reach 771 patients with either a positive TB patients and TB negative. Boarding was located in the hamlet Sanggrahan Manokwari, populated by students as much as 50 people. The data was obtained from the year 2005-2009 there were seven known TB patients in Manokwari Boarding Sleman, and some were suspected of showing symptoms of TB patients with a skinny body and the observation of TB team Puskesmas Depok II some of them did not perform to complete TB treatment or medication discontinuation (drop out). The purpose those study to determine the correlation between knowledge and attitudes about prevention of transmission of TB to the behavior of students in a dormitory at Manokwari Sleman, Yogyakarta. Methods:  This study used an analytical observation research with cross sectional design. The sampling technique used  the Totality of all population sampling as the sample of the research  was 50 people with variable measurements using questionnaires. Analyzed research data used univariate and bivariate. Results: The level of knowledge has a level of a very weak relation with the correlation coefficient of 0.21, determination coefficient of 0.000 means that the level of knowledge do not contribute to prevention of transmission of the behavior of students in a dormitory at Yogyakarta, Manokwari and sig 0.904> 0.05, which means there is no relationship between the level of knowledge about prevention of transmission of TB to the behavior of students in Yogyakarta, Manokwari Dormitory. Multiple Linear Correlation Results of 0.520 means to have the relationship that is, the coefficient of determination equal to 0.270 means that the attitude that contributed 27 percent of student behavior in the prevention of transmission in Yogyakarta, Manokwari Boarding and .001 Sig <.05, which means there was a correlation between attitudes about TB with the behavior of students in the prevention of transmission in Yogyakarta, Manokwari Dormitory. Conclusion:  There was no correlation between the levels of knowledge about prevention of transmission of TB to the behavior and there is a relationship between attitudes and behavior concerning prevention of transmission of tuberculosis in students in Yogyakarta, Manokwari Dormitory. Keywords: Knowledge, Attitude, Behavior, TBC